Childhood Hermeneutics and the Uniqueness of the Aesthetic Reading of Children's Literature - Stefania Carioli (University of Bologna, 2024)
The purpose of this paper is to reflect on the uniqueness of the aesthetic reading of children's literature and child hermeneutics as foundations for reading education. The first section examines Louise Rosenblatt's transactional model of aesthetic reading and Wolfgang Iser's phenomenological approach, as well as their theoretical implications for reader-response criticism. The paper's second section focuses on some more recent reader-response criticism research directions, which investigate postmodern picturebooks whose proposals within the educational scene have generated conflicting opinions. However, empirical studies that have investigated the point of view from which real children authentically live the experience of reading have demonstrated the surprising ability of younger readers to fathom and interpret these ambitious narratives, which invite readers into an experience that enhances interpretive resourcefulness. The characteristics of this variety of books reveal an implicit trust in the hermeneutic potential of younger readers, which contradicts the deep-rooted idea that continues to paint them as incapable of artistic-aesthetic experiences and unable to express their own hermeneutics.